Tudor Vianu, un comparatist atras de antichitate - Alexandra Ciocârlie (Revista de Istorie și Teorie Literară)
Tudor Vianu’s studies of world literature and comparative literature – some of which are synthetic, the others, analytic, some devoted to constructing an outline of the general evolution of literature, the others seeking a more in-depth approach to particular aspects of older or more recent literary texts – prove his constant interest in shedding light on the connections of the moderns with the ancients.